Energy trading systems on blockchain networks - Jae Geun Song; Ju Wook Jang (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
Traditional energy trading system has some weakness in terms of network attack. So blockchain is considered for P2P energy trading systems to evade network attacks. We consider three energy trading systems on blockchain which are centralized energy trading system with one producer, P2P energy trading system with DSO and P2P energy trading system with smart contract. And we compared P2P energy trading systems on running in terms of transaction fees. By using blockchain, users can reduce transaction fees then make more benefits.